2010
DOI: 10.1109/tbme.2010.2045757
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Tactile Imaging

Abstract: Changes in the elasticity of the vaginal walls, connective support tissues, and muscles are thought to be significant factors in the development of pelvic organ prolapse, a highly prevalent condition affecting at least 50% of women in the United States during their lifetimes. It creates two predominant concerns specific to the biomechanical properties of pelvic support tissues: how does tissue elasticity affect the development of pelvic organ prolapse and how can functional elasticity be maintained through rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 57 publications
4
35
0
Order By: Relevance
“…We observed that the vaginal wall was stiffer in cases than in controls. Results are consistent with data from a study using a proof of concept prototype of the vaginal tactile imager 25 and with data obtained by traditional uniaxial tension tests. 23 Overall the traditional uniaxial tension studies indicate that prolapse confers less elasticity and greater stiffness with low forces at failure.…”
Section: Discussionsupporting
confidence: 88%
“…We observed that the vaginal wall was stiffer in cases than in controls. Results are consistent with data from a study using a proof of concept prototype of the vaginal tactile imager 25 and with data obtained by traditional uniaxial tension tests. 23 Overall the traditional uniaxial tension studies indicate that prolapse confers less elasticity and greater stiffness with low forces at failure.…”
Section: Discussionsupporting
confidence: 88%
“…Its etiology is multifactorial and includes vaginal delivery as well as obesity, age, and menopause among the most common risk factors [2]. The anterior vaginal wall (AVW) compartment is the most commonly affected, resulting in a gradual descent of the bladder reaching to (stage II) or extending beyond (stage III) the vaginal introitus [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Certain studies were performed aimed at the improvement of force feedback in minimally invasive or robotic surgeries 7,8. However, the problem of tactile feedback was not adequately studied: the results were either preliminary from the viewpoint of clinical applications912 or not focused on surgery 13,14. At the same time, tactile feedback is essential for control of tissue interaction15 and cannot be completely substituted by visual or audio feedback 16,17…”
Section: Introductionmentioning
confidence: 99%